Missouri EATs: Cultivating community food systems through community engagement - William McKelvey; Pam Duitsman; Dean Larkin; Sarah Hultine Massengale; Jeff Samborski (Urban Food Systems Symposium, 2020)
The University of Missouri Extension Missouri EATs program connects local stakeholders to build and strengthen their community’s food system. Missouri EATs (which stands for Engage, Act, and Transform) is a community development program designed to engage people to identify local assets and needs; help them develop a plan to act on their top priorities; and make lasting changes to transform their local food system. The broad goal of Missouri EATs is to create healthy, resilient, and equitable community-based food systems. The starting point is a community-wide in-person or on-line forum for participants to engage in an informed and facilitated discussion about the food system. This event is the first step of a larger community organizing process that engages communities to make positive changes over time. The format allows for broad discussions related to local agriculture, hunger, health, and related topics. It relies heavily on local input from community members in general and those representing of local business and agencies. The forum results in a Food System Action Plan, which is a tool used to keep communities engaged after the event and guide their ongoing effort. Communities may choose to hold a combination of small working group meetings, community meals, or quarterly meetings to keep things moving in a positive direction. Annual meetings are encouraged to provide updates and reengage community members. The forum and subsequent activities may all be adapted for an on-line environment.
Keywords: development; action; planning; conversation; transformation; resilient